The Effect of Ginger (Zingiber OFFICINALE) on Reducing the Intensity of Hand Pain (Primy Dysmenorrhea) in Adolescent Women:: A Systematic Literature Review - Juwita, Juwita; Nurhaeda, Nurhaeda; Umar, Fadly (Universitas Muhammadiyah Kalimantan Timur, 2022)
Dysmenorrhea is lower abdominal pain that occurs during menstruation. According to the World Health Organization (WHO), 1,769,425 people (90%) experienced dysmenorrhea with an incidence of 10-15% of whom experienced dysmenorrhea with severe pain. Traditional medicine by consuming ginger can be an alternative as an effort to reduce menstrual pain (primary dysmenorrhea). The purpose of this study was to determine whether there was an effect of giving ginger (zingiber officinale) to decrease the intensity of menstrual pain (primary dysmenorrhea) in adolescent girls. The method used in this research is to use Systematic Literature Review (SLR). This study examines 9 journals for 2009-2021 consisting of 7 international journals and 2 national journals. All journals conducted studies related to the incidence of primary dysmenorrhea in adolescent girls. The original journal was obtained from the search results of the PuBmed and Google Scholar databases. The results of this study from 7 international journals and 2 national journals that have been studied can be seen that all research subjects, namely young women after giving the intervention experienced a significant decrease in menstrual pain (dysmenorrhea). This is because the active ingredients such as gingerol, shogaol, zingiberene in ginger rhizome can be used as antioxidants and anti-inflammatory.